UA-ICON with the NWP physics package (version ua-icon-2.1): mean state and variability of the middle atmosphere - M. Kunze; C. Zülicke; T. A. Siddiqui; T. A. Siddiqui; C. C. Stephan; Y. Yamazaki; C. Stolle; S. Borchert; H. Schmidt (Geoscientific Model Development)
The Icosahedral Nonhydrostatic (ICON) general circulation model with an upper-atmospheric extension (UA-ICON) in the configuration with the physics package for numerical weather prediction (NWP) is presented with optimized parameter settings for the non-orographic and orographic gravity wave drag (GWD) parameterizations as UA-ICON(NWP) (version ua-icon-2.1). We implemented optimized parameter settings for the GWD parameterizations to achieve more realistic mesosphere/lower thermosphere (MLT) temperatures and zonal winds. The parameter optimization is based on perpetual January simulations targeting the thermal and dynamic states of the MLT and the Northern Hemisphere stratosphere. The climatology and variability of the Northern Hemisphere stratospheric winter circulation improve widely when applying UA-ICON with the NWP physics package compared to UA-ICON with ECHAM physics. The thermal and dynamic states of the MLT of the re-tuned UA-ICON(NWP) are likewise improved compared with UA-ICON(NWP) using default settings. A statistical evaluation of UA-ICON(NWP) reveals a slight improvement in the stratosphere–mesosphere coupling compared to UA-ICON(ECHAM). The cold summer mesopause, the warm winter stratopause, and the related wind reversals are reasonably simulated. Furthermore, the GWD parameter optimization significantly improves the frequency of major sudden stratospheric warmings (SSWs). However, the seasonal distribution needs improvement, and the relative frequency of split-vortex SSWs is underestimated compared to reanalyses, as is the zonal wavenumber-2 preconditioning of SSWs. This indicates that zonal wavenumber-2 forcing in UA-ICON(NWP) is underrepresented. The analysis of migrating diurnal and semidiurnal tides in temperature shows good agreement of UA-ICON(NWP) with Sounding of the Atmosphere using Broadband Emission Radiometry (SABER)-derived tides, and the enhancement of the migrating semidiurnal tide during SSWs is represented well in UA-ICON(NWP).